2014
DOI: 10.1185/03007995.2014.918029
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis, comorbidities, and management of restless legs syndrome

Abstract: Although clinical diagnosis of RLS can be straightforward, diagnostic challenges may arise when patients present with comorbid conditions. Comorbidities of RLS include insomnia, depressive and anxiety disorders, and pain disorders. Differential diagnosis is particularly important, as some of the medications used to treat insomnia and depression may exacerbate RLS symptoms. Appropriate diagnosis and management of RLS symptoms may benefit patient well-being and, in some cases, may lessen comorbid disease burden.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
62
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(67 citation statements)
references
References 216 publications
(257 reference statements)
2
62
0
3
Order By: Relevance
“…Abnormal PLMI, or periodic leg movement syndrome, and restless leg syndrome are common afflictions affecting 5-15% of the general population (Earley and Silber 2014;Becker and Novak 2014;Winkelman et al 2013) and associated with insomnia in 50-85% of people (Becker and Novak 2014). We identified only two patients having cortical arousals secondary to periodic leg movement that were greater than expected age norms.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Abnormal PLMI, or periodic leg movement syndrome, and restless leg syndrome are common afflictions affecting 5-15% of the general population (Earley and Silber 2014;Becker and Novak 2014;Winkelman et al 2013) and associated with insomnia in 50-85% of people (Becker and Novak 2014). We identified only two patients having cortical arousals secondary to periodic leg movement that were greater than expected age norms.…”
Section: Discussionmentioning
confidence: 87%
“…Possible causes include central sleep apnoea (CSA) and obstructive sleep apnoea (OSA), respectively, seen in 22% and 17% of patients (Duning et al 2013), and restless legs secondary to painful peripheral neuropathy, reported in 36% patients (Dominguez et al 2007). In comparison 2-4% of the adult normal population have OSA (Epstein et al 2009), while 5-15% are affected by restless legs (Earley and Silber 2014;Becker and Novak 2014;Winkelman et al 2013). Furthermore, 2.7% of the population meet criteria for clinically significant restless leg syndrome (Winkelman et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…10 We found a familial pattern in 68% of our RLS population and a significant correlation between the presence of primary RLS among first-and second-degree relatives, the onset of symptoms before the age of 45 years, and slower progression of the disease. Presence or absence of a genetic component did not preclude patients from developing other disorders, notably hypertension (67%), hyperlipidemia (52%), arthritis (48%), neuropathy with chronic pain (41%), and sleep apnea (37%).…”
mentioning
confidence: 55%
“…3 Several population-based studies report the onset of RLS occurring prior to the age of 10 years in 8%-13%, and 20 years in 27%-38% of the RLS population, respectively. 10 In our small RLS population, 20% of RLS patients reported onset symptomology at the mean age of 14.4 years with sleep-onset insomnia/nocturnal awakenings being early manifestations of the disorder. However, the RLS age of diagnosis in these patients was not until 28 years.…”
Section: Discussionmentioning
confidence: 78%
“…Headache, fatigue, sleep disturbances, depression and anxiety are common in patients with FM and/or RLS and quality of life is adversely affected (10,34,35,45,46). Looking at the data from our study, the addition of FM symptoms on RLS symptoms causes significantly worse responses to questions ("How do you think your overall health is?"…”
Section: Discussionmentioning
confidence: 80%